The Influence of Socio-Economic Conditions on Family Food Consumption (Study: Fishermen's Households of Beneficiary Families (KPM) in East Wara District, Palopo City) - Tumangke, Rusli Emba; Idawati, Idawati; Sukriming Sapareng (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Family food security is a strategic issue, especially for fishing families who receive government food assistance (KPM). Socio-economic conditions such as gender, age, education, income, and access to food greatly determine food consumption patterns and diversification. This study uses a qualitative descriptive approach with a total sampling of 52 fishing families who received KPM in East Wara District, Palopo City. Primary data were obtained through surveys and interviews using questionnaires that included demographics, consumption patterns, income, and spending. The analysis was carried out descriptively by relating socio-economic factors to food consumption. The results showed that the majority of respondents were women (96%) with a dominant age over 41 years old (68%). The level of education is relatively low, where 37% have a junior high school education and 35% high school, with no college graduates. Food consumption patterns still rely heavily on marine fish as the main source of protein. However, food diversification is still limited due to low purchasing power and limited nutritional knowledge. Rice assistance from the government's food reserves has been proven to ease the burden of household expenditure on carbohydrate sources, thus potentially opening up space for budget allocation to other foods. Conclusion: These findings confirm that socio-economic and demographic factors greatly affect the consumption patterns of fishing families. Low education and purchasing power are the main obstacles to food diversification, while the dominance of women's roles provides opportunities for more effective nutrition interventions.